Educação ambiental na concepção da educação inclusiva para estudantes com baixa visão - Muniz, Veronica (Universidade Federal de São Carlos, 2025)
Inclusive environmental education seeks to integrate conservation values with adapted practices that consider the sensory needs of students with low vision. In this context, taxidermy stands out by enabling tactile experiences that enrich learning and promote inclusion. This research aimed to explore, through a literature review, the scientific production on inclusive environmental education for people with low vision/visual impairment from 2013 to 2023 and to propose activities with Taxidermized animals for inclusive education. This is a bibliographic, conducted through a survey in four databases: Scielo (Scientific Electronic Library), CAPES Journals Portal (Coordination for the Improvement of Higher Education Personnel), Google Scholar, and BDTD (Brazilian Digital Library of Theses and Dissertations), using combined keywords: environmental education and low vision, environmental education and taxidermy, environmental education and visual impairment, inclusive environmental education. The data were analyzed qualitatively and organized into thematic categories. The study revealed a lack of pedagogical approaches that connect sustainability practices with inclusion. Furthermore, it proposed activities that combine tactile and audiovisual resources to explore the anatomical and ecological characteristics of animals, promoting greater engagement and accessibility. It concludes that inclusive pedagogical practices can foster environmental awareness and strengthen the autonomy of students with visual impairments.
Environmental education in the concept of inclusive education for students with low vision
Keywords: Educação Ambiental Inclusiva; Taxidermia; Deficiência Visual; Inclusive environmental education; Taxidermy; Visual impairment; CIENCIAS BIOLOGICAS